Placenta (IntechOpen, 2018)
The placenta, amniotic fluid, umbilical cord, and cord blood can often be classified as pregnancy-specific biological substances with enormous applications in regenerative medicine. The Placenta includes eight chapters that provide readers with access to a range of information from basic mechanisms and assays to cutting-edge research investigating concerns for normal placentation. The book presents a comprehensive, translational look at all aspects of abnormal placentation and its effects on maternofetal axis. It follows the relationship between placenta-derived mesenchymal stromal cells and modulation of immunity, gene expression, and inflammation. It also covers additional information concerning the management of placental complications, placental therapy, and biological roles of antiinflammation and regeneration. The Placenta will be of interest to scientists, embryologists, physicians, and lay readers wishing to review recent developments in the field of the placenta.